Frontières tacites. Confrontations et accords dans les favelas de Rio de Janeiro - Carolina Christoph Grillo (Confins)
This paper addresses the spatial discontinuities produced by the dynamics of armed conflict and agreements between police, drug traffickers and robbers in the city of Rio de Janeiro, emphasizing the changes produced by the implantation of Units of Pacifying Police (UPP). Based on an ethnographical research conducted in favelas controlled by a drug trafficking faction before, throughout and after the occupation by the military police, this article analyzes the relations that result in the mapping of tacit partition of territories among urban violence actors. It is argued that, although strategies to fight the illegal drug market have been reformulated – from the model of topic police incursion operations to « pacification » –, either the social controls and drug trafficking have remained territorialized, disputing and negotiating over the spatial limits imposed on the conduction of illegal practices and the circulation of certain categories of people. It has been observed that the circumscriptions of drug trafficking activities, before correspondent to the favelas’ perimeter, have been constricted within them and become suppler, though the former selling point structure has been kept. Due to the fragility of the new local power arrangements, there has also been an increase on the controls exerted by drug traffickers over the practice of robbery, introducing new tensions to the criminal dynamics.